The Impact of Communication and Trust in Leadership on Workers' Compensation: A Case Study of Suka Ramai Coffee Shop in Tanjung Pinang City - Soraya Agustina Situmorang (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2023)
Human resources play a crucial role in every company, and managing them effectively is essential for creating a positive work environment. Human Capital Management (HCM) emphasizes the value of employees as assets that need to be professionally and sustainably managed. Proper management of employees can lead to significant benefits, including the ability to execute business strategies, create future opportunities, and enhance overall company competitiveness. This study examines the role of trust in leadership and communication in employee compensation. It adopts a descriptive qualitative approach, utilizing interview data and observations. The findings highlight the significance of trust in leaders for effective communication, which contributes to building trust among employees. When trust between leaders and employees is established, leaders can transparently provide fair compensation, which enhances employee motivation, performance, and loyalty to the company. The study underscores the importance of trust and communication in ensuring equitable compensation for employees.